Review: Current Checklist of Local Names and Utilization Information of Indonesian Wild Mushrooms - Ivan Permana Putra; Nicho Nurdebyandaru; Mega Putri Amelya; Rudy Hermawan (Universitas Gadjah Mada, 2022)
Mushrooms have been considered an important part of human life due to their various benefits and potential. In Indonesia, many indigenous people get used to foraging and using wild mushrooms as part of their daily lives. To date, there was no update following prior local name checklist of wild mushroom and their uses in Indonesia. Thus, this review aims to provide the latest work on that information known so far in the country. A literature review was focusing on available publications containing the local names and the use of wild mushrooms in Indonesia. 107 mushrooms in total are known to have 170 local names with 36 of them having more than 1 indigenous name. Some of them: Coprinus spp., Polyporus spp., Schizophyllum commune, Scleroderma spp., Termitomyces spp., and Trametes spp. are known to have 5 local names for each region and ethnicity that uses them. 50 species of mushrooms in total are used as food and traditional medicine. The information was derived from 8 provinces and 8 tribes, of which West Kalimantan Province and Javanese ethnicity contributed to the highest number of it. The number of local names is expected to increase as more investigations are conducted in the near future.